Beberapa Tantangan Pengembangan Agribisnis ke Depan - Darmadi Darmadi (Jurnal Dinamika Sosial Ekonomi, 2000)
The challenges for developing of agribisnis in Indonesia in the future is still big enough. Challenges can cime from foreign and domestic. The competition from foreign will be more felt eventually. Challenges from domestic connect with farmers agribisnis behaviour, it mean that human resources need change that aim from subsistence to commercial. The aversion to take risk means lost profit probability to increase. Technology for each subsistem from agribisnis process must be worked balanced in order to agribisnis system pass-off smoothly.Key word: Agribisnis system, human resources, profit